(untitled) (Journal of Asian Development Studies, 2015)
This study documents that fluctuations in the current monthly US retail sales are strongly affected by their lagged changes and changes in (i) Real Disposable Personal Income, (ii) S&P 500 equity index, (iii) University of Michigan Consumer Sentiment, (iv) Consumer Price Index for All Urban Consumers: All Items, (v) Civilian Unemployment Rate, (vi) Trade Weighted U.S. Dollar Index: Major Currencies, and (vii) lagged changes of these variables. The empirical findings, particularly the time lags, provide useful information for national policy makers to formulate their countercyclical policies and for retail sales management to predict their sales in order to effectively manage their operations.